Proof and Concepts in Rapid Diagnostic Tests and Technologies - Saxena, Shailendra K. (IntechOpen, 2016)
This book gives a comprehensive overview of the recent advancements and developments of rapid diagnostic tests (RDTs) and technologies, which are quite novel approaches and might be used as laboratory bench manual for the rapid diagnosis of the various disease conditions. The book focuses on various aspects and properties of RDTs, point-of-care tests (POCTs), quality control, assurance, calibration, safety, nano-/microfluidic technologies, and fusion with DNA technologies. I hope that this work might increase the interest in this field of research and that the readers will find it useful for their investigations, management, and clinical usage.